A study into the feasibility of consumers triggering factory robots to start production over the internet to optimize the current purchasing system - Prashobh, Karunakaran; Mohammad Shahril, Osman (SME, 2013)
This paper aims to study and justify the feasibility of developing a more efficient purchasing system due to the inefficiencies in the current system which is an economic waste and source of global warming. Today if products are not sold they are dumped by supermarkets, wholesalers, warehouses and factories. All this happens because of incorrect demand predictions. But if products are manufactured only after their credit cards has been debited there will not be a problem of incorrect demand prediction all along the supply chain. This will lead to a purchasing system where customers deal directly with factories, which is favorable to producers as well as customers because cost will go down and wastages will reduce.